THE HYDROGEN ISOTOPE COMPOSITION OF SEAWATER AND THE GLOBAL WATER CYCLE - Lécuyer C.; Gillet P.; Robert F. (My University, 1998)
Long-term evolution of the Earth's water cycle is investigated to predict potential variations in the hydrogen stable isotope composition of seawater. Mass balance calculations are used to estimate the δD value of the early ocean before storage of water (about 20% of the present-day size) in the biosphere, cryosphere, sediments, and metamorphic rocks. The early ocean was plausibly deuterium-depleted (δD=−18±6‰) in comparison with the present-day oceans (δD=0‰). A kinetic treatment of the long-term water cycle suggests that hydrogen isotope variations of the oceans may have occurred at a Ga time-scale in response to the imbalance between fluxes of water trapped at ridges and released along subduction zones. Two limiting cases are observed: (1) the δD value of the oceans does not exceed a value of +10‰ when the oceanic mass decreases by 20%; and (2) the δD value decreases down to −20‰ for a 20% mass increase of the oceans. An increase in the δD value of the planet via an addition of extraterrestrial water is restricted to 7‰ since 3.5 Ga. The present-day mean D/H ratio of the bulk Earth is calculated to be 149(±3)×10−6. Since the statistical distribution of the D/H ratios in carbonaceous chondrites exhibits a maximum value around 140±10×10−6, it is unlikely that the water D/H ratio was significantly fractionated during Earth's accretion relatively to the protosolar water ratio.